Sources De Financement Des Petites Et Moyennes Entreprises (PME) Et Contraintes De Survie - Anairi, Fadoua; Radi, Saïd (European Scientific Journal, ESJ, 2017)
The Small and Medium Enterprises (SMEs) play a very important role both in social and economic terms. To survive, these entities need adequate funding and ongoing support. This article aims to present the one hand the various sources of funding that can be used by SMEs, and secondly, it proposes to study the relationship-SME Bank, so as to identify the causes limiting the access to the bank loan, which is the most important source of funding for this category of companies.